Severe Trampoline Injuries: Incidence and Risk Factors in Children and Adolescents - Korhonen, Linda; Salokorpi, Niina; Suo-Palosaari, Maria; Pesälä, Juha; Serlo, Willy; Sinikumpu, Juha-Jaakko (European Journal of Pediatric Surgery, 2018)
Introduction Severe trampoline injuries in children and adolescents are rare; however, minor injuries are common and their incidence is increasing. Severe injuries are most commonly head and neck injuries. They may result in long-term morbidity. This study aimed to illustrate these severe injuries and to find out their incidence and risk factors.Materials and Methods This is a population-based, prospective study in the Oulu region of Finland completed over 2 years (May 1, 2015 to April 31, 2017). All children (<16 years of age) with severe trampoline injuries were included. Cervical spine fractures, chest wall and skull fractures, lesions of internal organs, hip and knee dislocations, and permanent disorders of the peripheral veins or nerves were in prior defined as severe. Multiple jumpers, stunts, younger age, previous injuries, insufficient use of safety equipment, and lack of supervision were hypothesized as risk factors.Results There were 11 injured patients (10 boys). The annual incidence was 6.28/100,000 children <16 years of age. Mean age was 11.5 years. Severe injuries included five ligamentous cervical spine injuries and two sternal bone fractures. In addition, there were one lumbar spine ligament injury, two hip dislocations, and one severe axillary plexus nerve lesion. Eight out of 11 accidents were not seen by any adult and none of them happened under professional supervision. Most injuries (N = 8) happened by failed backflips.Conclusion Most severe injuries happened in unsuccessful flips. Children should have an adult supervisor and flips should not be attempted.
Keywords: trampoline injuries; cervical spine injury; risk factors; severe; children